International Endometrial Tumor Analysis (IETA) terminology in women with postmenopausal bleeding and sonographic endometrial thickness ≥ 4.5 mm: agreement and reliability study. (7th February 2018) - Sladkevicius, P.; Installé, A.; Van Den Bosch, T.; Timmerman, D.; Benacerraf, B.; Jokubkiene, L.; Di Legge, A.; Votino, A.; Zannoni, L.; De Moor, B.; De Cock, B.; Van Calster, B.; et al.
ABSTRACT: Objective: To estimate intra‐ and interrater agreement and reliability with regard to describing ultrasound images of the endometrium using the International Endometrial Tumor Analysis (IETA) terminology. Methods: Four expert and four non‐expert raters assessed videoclips of transvaginal ultrasound examinations of the endometrium obtained from 99 women with postmenopausal bleeding and sonographic endometrial thickness ≥ 4.5 mm but without fluid in the uterine cavity. The following features were rated: endometrial echogenicity, endometrial midline, bright edge, endometrial–myometrial junction, color score, vascular pattern, irregularly branching vessels and color splashes. The color content of the endometrial scan was estimated using a visual analog scale graded from 0 to 100. To estimate intrarater agreement and reliability, the same videoclips were assessed twice with a minimum of 2 months' interval. The raters were blinded to their own results and to those of the other raters. Results: Interrater differences in the described prevalence of most IETA variables were substantial, and some variable categories were observed rarely. Specific agreement was poor for variables with many categories. For binary variables, specific agreement was better for absence than for presence of a category. For variables with more than two outcome categories, specific agreement for expert and non‐expert raters was best for not‐defined endometrial midline (93% and 96%), regular endometrial–myometrial junction (72% and 70%) and three‐layer endometrial pattern (67% and 56%). The grayscale ultrasound variable with the best reliability was uniform vs non‐uniform echogenicity (multirater kappa (κ), 0.55 for expert and 0.52 for non‐expert raters), and the variables with the lowest reliability were appearance of the endometrial–myometrial junction (κ, 0.25 and 0.16) and the nine‐category endometrial echogenicity variable (κ, 0.29 and 0.28). The most reliable color Doppler variable was color score (mean weighted κ, 0.77 and 0.69). Intra‐ and interrater agreement and reliability were similar for experts and non‐experts. Conclusions: Inter‐ and intrarater agreement and reliability when using IETA terminology were limited. This may have implications when assessing the association between a particular ultrasound feature and a specific histological diagnosis, because lack of reproducibility reduces the reliability of the association between a feature and the outcome. Future studies should investigate whether using fewer categories of variable or offering practical training could improve agreement and reliability. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2018; 51: 167–168